(untitled) (Journal of Tropical Pharmacy and Chemistry, 2025)
Background: Colorectal cancer (CRC) constitutes a major public health burden in Indonesia. Chemotherapy remains the primary treatment for advanced CRC but creates substantial financial pressure on patients, hospitals, and the National Health Insurance (JKN) system. Although reimbursement is provided through the Indonesia Case Base Groups (INA-CBGs), differences between actual costs and tariff rates have been reported. Objective: This study assessed the financial burden of chemotherapy for stage III and metastatic CRC and its alignment with JKN reimbursement in a government referral hospital in Kalimantan. Methods: A retrospective cross-sectional study was conducted at Abdoel Wahab Sjahranie Regional General Hospital, Samarinda, using medical records from January-June 2024. A total of 129 chemotherapy visits were analyzed. Direct medical costs were compared with INA-CBG claims using descriptive statistics and the Mann–Whitney U test. Results: FOLFIRI was the most frequently administered regimen (71%). The total chemotherapy cost was Rp590,674,630, with a mean of Rp4,578,873 per visit. Pharmaceutical costs accounted for 56.58% of total expenditures. Actual costs were adequately covered by JKN, resulting in a positive variance of Rp1,314,544 per visit. Conclusion: INA-CBG reimbursement adequately covered CRC chemotherapy costs, although continued evaluation of JKN financing sustainability is warranted.